Organ donation survey results of a Buffalo, New York, African-American community. - Minniefield, William J. (National Medical Association, 2002)
In order to evaluate general patterns of attitudes relating to organ donation based on age and educational levels in a typical northeast urban African American community, a survey was conducted in Buffalo, NY, a city with a high African American presence. Data for this study was obtained from a seven-question survey. The participants in the survey consisted of 173 African American respondents, 96 females and 77 males. Organ donation awareness was high, with 88% of the participants being familiar with organ donation. The 25- to 35-year-olds were more familiar than the other age groups. Thirty-six percent of the sample indicated they would not donate organs, 31% would donate, and 33% were unsure. Educational levels were a factor in the decision of whether to donate. Of the sample that would not donate organs, 35% had 12 or fewer years of formal education. Seventy-one percent admitted their family did not discuss organ donation. The 18- to 24-year-olds had the highest rate of lack of family discussion. The 36- to 73-year-olds most often cited religious reasons for not donating. The fear that their organs would be taken before they were dead was the rationale chosen more by the 18 to 24-year-olds. One hundred percent of the 25- to 35-year-olds were afraid they would not receive proper medical attention if they were organ donors. Thirty-two percent of the sample stated that they did not trust doctors; 24% indicated trust; and 44% indicated little trust. Awareness of being a living donor was lowest for the 25- to 35-year-olds--36% stating that they were not aware of this option. Seventy percent of the 18- to 24-year-olds believed that organs would go to select people and not to those who really need them.